Pendampingan Pengelolaan Pembelajaran Al-qur’an Santri Pondok Pesantren Darul Fatihin Pada Masa Pandemi Covid-19 di Desa Badas - Innani Muslimatun; Fadhil Akbar (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
PKM research program of The Islamic Institute faqih Asy'ari is a program of activities carried out from home, serving for the benefit of the Ummah. The purpose of the PKM Research program is to provide students with experience, knowledge, abilities, and awareness of community life, as well as prepare undergraduate candidates who are able to do online-based social change work. This research takes the theme of learning the Qur'an, which is a learning activity that has the goal that a person is able to read and write the Qur'an where the person can see, read, recite, and also make letters from the writings contained in the Holy Qur'an. This research was carried out during the covid pandemic, because of our limitations in all community service, one of the activities this time was to hold a lesson in Ponpes Darul Fatihin and I focused on learning the Qur'an. In an increasingly modern era, the hope of parents to their children is to have a better quality in the field of religion, especially read the Qur'an. However, the lack of interest of students in learning to read the Quran is felt right by teachers who in this day and age children are more busy with playing gadgets in their homes. So, in this case learning and understanding the science of Reading the Qur'an is very necessary in accordance with the rules of tajwid science where the law of studying the science of tajwid, tartil and tahsin is mandatory 'ain. The results of research on the BTA learning program in Ponpes Darul Fatihin is, the program is implemented in Ponpes Dael Fatihin which runs in accordance with what is expected although there are certainly a few obstacles as outlined earlier. The changes that occur in students after the program proves that the program has been able to change the progress of students in terms of spirituality. Students are already able to read the Qur'an well in accordance with the rules of the tajwid laws that he has learned.